A method for recovering ferric phosphate from crude ferric phosphate slag

By adding deionized water and reducing agent to the crude iron phosphate slag, combined with acid and oxidizing agent, the efficient leaching of iron and phosphorus components and the recovery of anhydrous iron phosphate are successfully achieved, and the low resource recovery efficiency in the prior art has been solved. The problem is that the product purity reaches the battery level.

CN118047360BActive Publication Date: 2025-02-18CENT SOUTH UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410282960.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-13
Publication Date
2025-02-18
Estimated Expiration
2044-03-13

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently leach iron-phosphorus components from crude iron phosphate slag, resulting in low resource recovery efficiency.

Method used

The leaching of the iron phosphorus component is achieved by mixing the crude iron phosphate slag with deionized water and reducing agent at room temperature, and adding acid to adjust the pH after the temperature is raised. Subsequently, an oxidant and alkali are added for precipitation, and finally anhydrous iron phosphate is obtained by aging and drying steps.

Benefits of technology

It realizes efficient leaching and recycling of iron and phosphorus components in crude iron phosphate slag, and the purity of the product reaches the battery level, solving the problem of low resource recovery efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118047360B_ABST
    Figure CN118047360B_ABST
Patent Text Reader

Abstract

The invention discloses a method for recovering ferric phosphate from crude ferric phosphate slag, which comprises the following steps: S1, adding the crude ferric phosphate slag into deionized water, stirring evenly, then adding a reducing agent, heating up for reaction, and obtaining slurry after the reaction is completed; S2, adding acid into the slurry obtained in step S1, stirring evenly, adjusting the pH value to 0.8-1.0, then heating up for leaching, and separating to obtain a leachate after the leaching is completed; S3, adding an iron-containing compound into the leachate obtained in step S2, then adding an oxidant for reaction, adding alkali after the reaction is completed, adjusting the pH value to 1.7-2.3, heating up for precipitation, and separating to obtain a synthetic filter cake after the precipitation is completed; S4, dispersing the synthetic filter cake obtained in step S3 into deionized water, then adding an aging agent, heating up for crystallization under stirring conditions, until the material turns into white crystals, and separating to obtain an aged filter cake; S5: drying and sintering the aged filter cake obtained in step S4 to obtain anhydrous ferric phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery recycling, and in particular relates to a method for recycling iron phosphate from crude iron phosphate slag. Background Art

[0002] Lithium-ion batteries are widely used in pure / hybrid electric vehicles and various electronic devices due to their advantages such as high operating voltage, long cycle life, and no memory effect. Among them, lithium iron phosphate batteries, as a simple and safe power source, have high cycle performance and do not contain precious metals. They occupy a large market share in power batteries, and their demand in the fields of new energy, base station energy storage, etc. is growing explosively. However, the service life of lithium-ion batteries is generally 5 to 7 years, and a large number of waste lithium iron phosphate batteries will be generated in the next few years. Lithium iron phosphate positive electrode materials are the most valuable in battery cells, and the large amount of crude iron phosphate slag produced in the wet lithium extraction process of waste lithium iron phosphate has not yet been efficiently recycled.

[0003] Improving the economic efficiency of recycling retired batteries lies in preparing the lithium, iron and phosphorus components in waste lithium iron phosphate cathode materials into battery-grade lithium salts and iron phosphate products through chemical methods, achieving efficient recovery and high-value utilization of lithium, iron and phosphorus components, which can be used as raw materials for preparing new lithium iron phosphate cathode materials. Therefore, there is a great challenge in how to efficiently leach the iron and phosphorus components in crude iron phosphate slag without losing iron and phosphorus. Summary of the invention

[0004] The present invention is intended to solve the technical problems existing in the above-mentioned prior art.

[0005] To this end, the present invention discloses a method for recovering iron phosphate from crude iron phosphate slag, comprising the following steps:

[0006] S1, adding crude iron phosphate slag into deionized water at room temperature, stirring evenly, then adding a reducing agent, heating to 50-90° C. to react, and obtaining a slurry after the reaction is completed;

[0007] S2, adding acid to the slurry obtained in step S1 at room temperature, stirring evenly, adjusting the pH value to 0.8-1.0, and then heating to 70-90° C. for leaching, and separating to obtain a leachate after the leaching is completed;

[0008] S3, at room temperature, adding an iron-containing compound to the leachate obtained in step S2, so that the total iron element and the total phosphorus element in the iron-containing compound and the leachate meet the stoichiometric ratio of the iron element to the phosphorus element in the ferric phosphate, then adding an oxidant to react, adding an alkali after the reaction, adjusting the pH value to 1.7-2.3, raising the temperature to 50-90° C. for precipitation, and separating to obtain a synthetic filter cake after the precipitation;

[0009] S4, dispersing the synthetic filter cake obtained in step S3 in deionized water at room temperature, then adding an aging agent, and then heating to 50-90° C. to crystallize under stirring until the material turns crystal white, and separating to obtain an aged filter cake;

[0010] S5: drying and sintering the aged filter cake obtained in step S4 to obtain anhydrous ferric phosphate.

[0011] In some embodiments, in step S1, the crude iron phosphate slag is waste lithium iron phosphate black powder lithium extraction slag, which is produced after lithium is extracted from the crude iron phosphate slag.

[0012] In some embodiments, in step S1, the liquid-to-solid ratio of the deionized water to the crude ferric phosphate slag is 5 to 10:1 mL / g.

[0013] In some embodiments, in step S1, the stirring process parameters are: stirring speed is 300-400 r / min, and time is 20-30 min.

[0014] In some embodiments, in step S1, the reducing agent is at least one of a sulfite or a sulfide salt.

[0015] In some embodiments, in step S1, the reducing agent is at least one of sodium bisulfite, sodium sulfite, sodium sulfide, and sodium bisulfide.

[0016] In some embodiments, in step S1, the amount of the reducing agent is 0.4 to 1 times the molar amount of the iron element in the crude iron phosphate slag. Preferably, the amount of the reducing agent is 0.5 to 0.7 times the molar amount of the iron element in the crude iron phosphate slag. In other embodiments, the amount of the reducing agent is 0.5, 0.6, or 0.7 times the molar amount of the iron element in the crude iron phosphate slag. The reducing agent is used to lower the potential of the system so that the ferric phosphate structure is completely converted into a ferrous phosphate structure, and the subsequent addition of a small amount of acid can achieve the dissolution of iron and phosphorus; if the ratio is greater than 1, too much reducing agent will cause the pH of the system to increase, and the acid consumption will increase significantly in the next step, with low efficiency and high cost.

[0017] In some embodiments, in step S1, the reaction time is 1 to 3 hours.

[0018] In some embodiments, in step S2, the acid is at least one of sulfuric acid, phosphoric acid, nitric acid, and hydrochloric acid.

[0019] In some embodiments, in step S2, the leaching time is 1 to 2 hours.

[0020] In some embodiments, in step S2, the separation includes: filtering the mixture after uniform stirring to obtain an iron-phosphorus-containing leaching solution.

[0021] In some embodiments, in step S3, the iron-containing compound is at least one of a ferric salt, a ferrous salt, and an iron oxide.

[0022] In some embodiments, in step S3, the iron-containing compound is at least one of ferrous sulfate, ferric sulfate, and iron oxide.

[0023] In some embodiments, in step S3, the oxidant is at least one of hydrogen peroxide and ammonium persulfate.

[0024] In some embodiments, in step S3, the amount of the oxidant is 0.7 to 1 times the molar amount of the total iron element in the iron-containing compound and the leachate. Preferably, the amount of the oxidant is 0.7 to 0.9 times the molar amount of the total iron element in the iron-containing compound and the leachate. In other embodiments, the amount of the oxidant is 0.7, 0.8, or 0.9 times the molar amount of the iron element in the crude ferrophosphate slag.

[0025] In some embodiments, in step S3, the oxidant is added for a reaction time of 15 to 30 minutes.

[0026] In some embodiments, in step S3, the base is at least one of sodium hydroxide or ammonia water.

[0027] In some embodiments, in step S3, the precipitation time is 1 to 3 hours.

[0028] In some embodiments, in steps S3 and S4, the separation includes: filtering the liquid to obtain a filter cake, and washing the filter cake multiple times with deionized water.

[0029] In some embodiments, in step S4, the aging agent is at least one of sulfuric acid or phosphoric acid. The formation of iron phosphate precipitation is affected by dissolution equilibrium and ionization equilibrium. By controlling the ratio of phosphoric acid and phosphate in the synthetic filter cake dispersion liquid, the hydrogen ion concentration is increased, and the phosphate radical in the iron phosphate is more easily hydrolyzed into phosphoric acid molecules. Under this condition, the dissolution and recrystallization process of the iron phosphate precipitation is delayed, so that the grain size after crystallization is smaller.

[0030] In some embodiments, the molar amount of the aging agent is 0.1 to 0.3 times the molar amount of the iron element in the synthetic filter cake. Preferably, the molar amount of the aging agent is 0.1 times the molar amount of the iron element in the synthetic filter cake.

[0031] In some embodiments, the crystallization time is 1 to 3 hours.

[0032] In some embodiments, in step S4, the temperature is raised to 90° C. and crystallization is performed under stirring conditions at a stirring speed of 300 to 400 r / min. Preferably, the crystallization temperature is 90° C. By increasing the temperature, the solubility of the iron phosphate precipitate is increased, the dissolution and recrystallization process of the iron phosphate precipitate is delayed, and the grain size after crystallization is smaller.

[0033] In some embodiments, in step S4, the material turns crystal and white, and the stirring speed is reduced to 200-300 r / min.

[0034] In some embodiments, in step S4, the drying comprises: placing the aged filter cake in an oven and drying it at 120° C. to obtain ferric phosphate dihydrate.

[0035] In some embodiments, in step S4, the sintering includes: placing ferric phosphate dihydrate in a muffle furnace and sintering at 560° C. to obtain a finished anhydrous ferric phosphate product.

[0036] The beneficial effects of the present invention are:

[0037] (1) The present invention reduces the trivalent iron in the ferric phosphate to divalent iron by adding a reducing agent to the crude ferric phosphate slag solution, thereby destroying the stable ferric phosphate structure and facilitating the occurrence of reduction leaching reaction.

[0038] (2) The present invention adds acid to allow the divalent iron and phosphate ions to separate from the unstable ferrous phosphate structure in an acidic environment, forming ferrous salts and phosphate ions that are leached into the solution, thereby achieving complete leaching of the iron and phosphorus components in the crude ferric phosphate slag.

[0039] (3) The present invention adopts a reduction acid leaching process, which has mild conditions and can suppress other impurity ions in the carbon slag. The iron-phosphorus components are precipitated into iron phosphate through an oxidant and an alkaline agent, thereby making the anhydrous iron phosphate product have high purity and reach battery-grade iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0041] Figure 1 This is the XRD diagram of the anhydrous ferric phosphate product prepared in Example 1 of the present invention.

[0042] Figure 2 This is a SEM image of the anhydrous ferric phosphate product prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0044] First, some nouns or terms that appear in the description of the present invention are explained as follows:

[0045] The term "and / or" in this article only describes an association relationship, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone.

[0046] The term "at least one" herein means any combination of at least two of any one or more of a plurality of types, for example, including at least one of A, B, and C, and may mean any one or more elements selected from the set consisting of A, B, and C.

[0047] The term "room temperature" herein refers to ambient temperature, which is from about 10°C to about 40°C. In some embodiments, "room temperature" refers to a temperature from about 20°C to about 30°C; in other embodiments, "room temperature" refers to a temperature from about 25°C to about 30°C; in still other embodiments, "room temperature" refers to 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc.

[0048] The test method in the embodiment of the present invention:

[0049] 1) Iron molar amount test

[0050] The mass of iron in the lithium extraction slag or leaching solution is tested by an inductively coupled plasma emission spectrometer, and the molar amount of iron is the mass obtained by the test divided by the relative atomic mass of iron.

[0051] 2) Leaching rate test

[0052] The leaching rate of iron and phosphorus in the lithium iron phosphate slag leaching process refers to the percentage ratio of the difference between the content of iron and phosphorus in the lithium extraction slag and the content of iron and phosphorus in the leached slag to the content of iron and phosphorus in the lithium extraction slag.

[0053] 3) Sedimentation rate test

[0054] The precipitation rate of iron and phosphorus in the ferric phosphate precipitation process refers to the percentage ratio of the difference between the content of iron and phosphorus in the liquid before precipitation and the content of iron and phosphorus in the liquid after precipitation to the content of iron and phosphorus in the liquid before precipitation.

[0055] 4) Impurity content test

[0056] The mass of impurities in the anhydrous ferric phosphate product is tested by an inductively coupled plasma emission spectrometer, and the impurity content is the mass of the impurities obtained by the test divided by the total mass of the anhydrous ferric phosphate product.

[0057] 5) SEM test

[0058] Scanning electron microscopy (SEM) is a microscopic technique between projection electron microscopy and optical microscopy. It processes the physical signals generated when a finely focused electron beam is scanned, thereby observing the microscopic morphology of the surface of a solid material. The present invention uses a Sigma300 scanning electron microscope produced by Carl Zeiss Optoelectronic Technology Co., Ltd. of Germany.

[0059] 6) XRD test

[0060] X-ray diffractometer (XRD) mainly uses X-ray to irradiate materials, collect diffraction patterns, process patterns with Jade software, and obtain information such as material composition, phase composition, and crystallinity of unit cells from the patterns. The present invention uses XRD-7000S X-ray diffractometer produced by Shimadzu Corporation of Japan. The scanning range is 10-120°, the scanning step length is 0.0065°, and the Kal wavelength is

[0061] Example 1

[0062] The embodiment of the present invention provides a method for recovering iron phosphate from crude iron phosphate slag, comprising the following steps:

[0063] S1, washing and drying the slag produced after lithium extraction from the waste lithium iron phosphate battery black powder to obtain crude iron phosphate slag.

[0064] S2, at room temperature, the crude iron phosphate slag obtained in step S2 was stirred and mixed with deionized water at a solid-liquid ratio of 200 g / L, the stirring speed was 350 r / min, and the stirring time was 30 min. The mixed solution was heated to 90°C, sodium bisulfite was added, and the mixture was kept warm for 2 hours to reduce the trivalent iron in the iron phosphate to divalent iron, and a slurry was obtained after the reaction was completed.

[0065] The molar amount of sodium bisulfite is 1 times the molar amount of iron in the crude ferrophosphate slag.

[0066] S3, add sulfuric acid solution to the slurry obtained in step S2, adjust the pH value of the slurry system to 0.8, stir evenly after the addition is completed and confirm the pH value, then heat to 90°C for leaching for 2h, filter and wash, and separate the filtrate containing iron and phosphorus components and carbon slag.

[0067] The leaching rates of the leaching reaction are: iron element Fe 97.9%, phosphorus element P 96.0%.

[0068] The process flow for leaching iron and phosphorus components from crude iron phosphate slag disclosed by the invention is simple and easy to operate, and can be applied to industry on a large scale.

[0069] S4, taking the leachate obtained in step S3, adding ferrous sulfate solution to make up the corresponding feed ratio, mixing evenly, adding hydrogen peroxide to the mixed solution, reacting for 30 minutes, reoxidizing the divalent iron in the leachate to trivalent iron, and then adjusting the pH value of the solution to 1.7 with an ammonia solution, stirring for 10 minutes to confirm the pH value, and then heating to 50°C for precipitation, keeping the temperature for reaction for 1 hour, filtering after the reaction to obtain a synthetic filter cake and a synthetic mother liquor. The synthetic filter cake is washed with deionized water.

[0070] The molar amount of hydrogen peroxide is 0.7 times the molar amount of iron in the mixed solution.

[0071] S5, adding the washed synthetic filter cake into deionized water, breaking and stirring evenly, adding phosphoric acid, then heating to 90°C and crystallizing under stirring conditions until the material turns crystal and white, lowering the stirring speed and keeping the temperature for reaction for 1 hour, filtering after the reaction to obtain aged filter cake and aged mother liquor. The aged filter cake is washed with deionized water.

[0072] The molar amount of phosphoric acid is 0.3 times the molar amount of iron in the synthetic filter cake.

[0073] The total precipitation rate of step S4 and step S5 is: iron element Fe 97.5%, phosphorus element P 94.9%.

[0074] S6, placing the washed aged filter cake in an oven, drying at 120° C. for 18 hours to obtain ferric phosphate dihydrate. Placing the ferric phosphate dihydrate in a muffle furnace and sintering at 560° C. to obtain anhydrous ferric phosphate finished product.

[0075] The copper element Cu content in the finished anhydrous ferric phosphate product is 0.0003%, the nickel element Ni content is not detected ND, the cobalt element Co content is 0.0003%, and the zinc element Zn content is 0.0004%.

[0076] Figure 1 This is an X-ray diffraction characterization diagram of the anhydrous ferric phosphate product prepared in this example. Figure 2 This is a scanning electron microscope image of the anhydrous ferric phosphate product prepared in this example.

[0077] As can be seen from the figure, the finished anhydrous ferric phosphate product prepared in this embodiment is a dense flaky structure with uniform particle size.

[0078] Example 2

[0079] The embodiment of the present invention provides a method for recovering iron phosphate from crude iron phosphate slag, comprising the following steps:

[0080] S1, washing and drying the slag produced after lithium extraction from the waste lithium iron phosphate battery black powder to obtain crude iron phosphate slag.

[0081] S2, at room temperature, the crude iron phosphate slag obtained in step S2 is stirred and mixed with deionized water at a solid-liquid ratio of 100 g / L, the stirring speed is 300 r / min, and the stirring time is 20 min. The mixed solution is heated to 50° C., sodium sulfite is added, and the mixture is kept warm for 3 hours to reduce the trivalent iron in the iron phosphate to divalent iron, and a slurry is obtained after the reaction is completed.

[0082] The molar amount of sodium sulfite is 0.4 times the molar amount of iron in the crude ferrophosphate slag.

[0083] S3, add nitric acid solution to the slurry obtained in step S2, adjust the pH value of the slurry system to 1.0, stir evenly after the addition is completed and confirm the pH value, then heat to 70°C for leaching for 1.5h, filter and wash, and separate the filtrate containing iron and phosphorus components and carbon slag.

[0084] The leaching rates of the leaching reaction were: 98.3% for Fe element and 96.0% for P element.

[0085] S4, taking the leachate obtained in step S3, adding ferric sulfate solution to make up the corresponding feed ratio, mixing evenly, dropping hydrogen peroxide into the mixed solution, reacting for 15 minutes, reoxidizing the divalent iron in the leachate to trivalent iron, and then adjusting the pH value of the solution to 2.0 with an ammonia solution, stirring for 10 minutes to confirm the pH value, and then heating to 90°C for precipitation, keeping the temperature for reaction for 3 hours, and filtering after the reaction to obtain a synthetic filter cake and a synthetic mother liquor. The synthetic filter cake is washed with deionized water.

[0086] The molar amount of hydrogen peroxide is 0.7 times the molar amount of iron in the mixed solution.

[0087] S5, adding the washed synthetic filter cake into deionized water, breaking and stirring evenly, adding sulfuric acid, then heating to 50°C and crystallizing under stirring conditions until the material turns crystal and white, lowering the stirring speed and keeping the temperature for reaction for 3 hours, filtering after the reaction to obtain aged filter cake and aged mother liquor. The aged filter cake is washed with deionized water.

[0088] The molar amount of sulfuric acid is 0.1 times the molar amount of iron in the synthetic filter cake.

[0089] The total precipitation rate of step S4 and step S5 is: 96.9% of Fe element and 95.3% of P element.

[0090] S6, placing the washed aged filter cake in an oven, drying at 120° C. for 18 hours to obtain ferric phosphate dihydrate. Placing the ferric phosphate dihydrate in a muffle furnace and sintering at 560° C. to obtain anhydrous ferric phosphate finished product.

[0091] The Cu content in the finished anhydrous ferric phosphate is ND, the Ni content is not detected ND, the Co content is 0.0003%, and the Zn content is 0.0004%.

[0092] Example 3

[0093] The embodiment of the present invention provides a method for recovering iron phosphate from crude iron phosphate slag, comprising the following steps:

[0094] S1, washing and drying the slag produced after lithium extraction from the waste lithium iron phosphate battery black powder to obtain crude iron phosphate slag.

[0095] S2, at room temperature, the crude iron phosphate slag obtained in step S2 was stirred and mixed with deionized water at a solid-liquid ratio of 150 g / L, the stirring speed was 400 r / min, and the stirring time was 25 min. The mixed solution was heated to 70°C, sodium sulfide was added, and the mixture was kept warm for 1 hour to reduce the trivalent iron in the iron phosphate to divalent iron, and a slurry was obtained after the reaction was completed.

[0096] The molar amount of sodium sulfide is 0.7 times the molar amount of iron in the crude ferrophosphate slag.

[0097] S3, adding phosphoric acid solution to the slurry obtained in step S2, adjusting the pH value of the slurry system to 0.9, stirring evenly after the addition is completed and confirming the pH value, then heating to 80°C for leaching for 1 hour, filtering and washing, and separating to obtain a filtrate containing iron and phosphorus components and carbon slag.

[0098] The leaching rates of the leaching reaction were: 99.9% for Fe element and 99.0% for P element.

[0099] S4, taking the leachate obtained in step S3, adding iron oxide to make up the corresponding feed ratio, mixing evenly to fully dissolve the iron oxide, dropping ammonium persulfate solution into the mixed solution, reacting for 20 minutes, reoxidizing the divalent iron in the leachate to trivalent iron, and then adjusting the pH value of the solution to 2.3 with sodium hydroxide solution, stirring for 10 minutes to confirm the pH value, and then heating to 70°C for precipitation, keeping the temperature for reaction for 2 hours, and filtering after the reaction to obtain a synthetic filter cake and a synthetic mother liquor. The synthetic filter cake is washed with deionized water.

[0100] The molar amount of ammonium persulfate is 0.9 times the molar amount of iron in the mixed solution.

[0101] S5, adding the washed synthetic filter cake into deionized water, breaking and stirring evenly, adding sulfuric acid, then heating to 70°C and crystallizing under stirring conditions until the material turns crystal and white, lowering the stirring speed and keeping the temperature for reaction for 2 hours, filtering after the reaction to obtain aged filter cake and aged mother liquor. The aged filter cake is washed with deionized water.

[0102] The molar amount of sulfuric acid is 0.2 times the molar amount of iron in the synthetic filter cake.

[0103] The total precipitation rate of step S4 and step S5 is: 97.4% of Fe element and 94.3% of P element.

[0104] S6, placing the washed aged filter cake in an oven, drying at 120° C. for 18 hours to obtain ferric phosphate dihydrate. Placing the ferric phosphate dihydrate in a muffle furnace and sintering at 560° C. to obtain anhydrous ferric phosphate finished product.

[0105] The Cu content in the finished anhydrous ferric phosphate is 0.0002%, the Ni content is ND, the Co content is 0.0002%, and the Zn content is 0.0001%.

[0106] Comparative Example 1

[0107] The difference between Comparative Example 1 and Example 1 is that: in step S2, no reducing agent is added to reduce the trivalent iron. In step S3, the leaching reaction is directly carried out under acidic conditions.

[0108] The test results of comparative example 1:

[0109] In step S2, the leaching rates of the leaching reaction are: 49.7% of Fe element and 45.8% of P element.

[0110] The total precipitation rate of step S4 and step S5 is: 97.2% of Fe element and 94.6% of P element.

[0111] The finished product of anhydrous ferric phosphate contains 0.01% Cu, 0.01% Ni, 0.02% Co and 0.01% Zn.

[0112] Comparing the test results, it can be seen that, on the one hand, since the reducing agent used in the present application can promote the conversion of trivalent iron ions to divalent iron ions, it is beneficial to the occurrence of reduction leaching reaction. On the other hand, the addition of the reducing agent can also inhibit the leaching of other impurity metal ions; since no reducing agent is added in an acidic environment, the leaching rate of comparative example 1 is low, which is only 49.7% of Fe element and 45.8% of P element, which is lower than 97.9% of Fe element and 96.0% of P element in Example 1, which is about 50% lower. Moreover, the impurity content in the finished anhydrous ferric phosphate of comparative example 1 is significantly higher than that of Example 1.

[0113] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for recovering ferric phosphate from crude ferric phosphate slag, characterized in that: The following steps are involved: S1, washing and drying the slag produced after extracting lithium from the waste lithium iron phosphate battery black powder to obtain crude iron phosphate slag; S2, at room temperature, the crude iron phosphate slag obtained in step S1 was stirred and mixed with deionized water at a solid-liquid ratio of 150 g / L, the stirring speed was 400 r / min, the stirring time was 25 min, the mixed solution was heated to 70°C, sodium sulfide was added, and the mixture was kept warm for 1 hour to reduce the trivalent iron in the iron phosphate to divalent iron. After the reaction, a slurry was obtained, wherein the molar amount of sodium sulfide was 0.7 times the molar amount of iron in the crude iron phosphate slag; S3, at room temperature, adding phosphoric acid solution to the slurry obtained in step S2, adjusting the pH value of the slurry system to 0.9, stirring evenly after the addition is completed and confirming the pH value, then heating to 80° C. for leaching for 1 hour, filtering and washing, and separating to obtain a filtrate containing iron and phosphorus components and carbon slag; S4, at room temperature, taking the leachate obtained in step S3, adding an iron-containing compound so that the total iron and total phosphorus in the iron-containing compound and the leachate satisfy the stoichiometric ratio of iron to phosphorus in ferric phosphate, mixing evenly, dissolving the iron-containing compound fully, dropping an ammonium persulfate solution into the mixed solution, reacting for 20 minutes, reoxidizing the divalent iron in the leachate to trivalent iron, and then adjusting the pH value of the solution to 2.3 with a sodium hydroxide solution, stirring for 10 minutes to confirm the pH value, and then heating to 70°C for precipitation, keeping the temperature for reaction for 2 hours, filtering after the reaction to obtain a synthetic filter cake and a synthetic mother liquor, and washing the synthetic filter cake with deionized water, wherein the molar amount of ammonium persulfate is 0.9 times the molar amount of iron in the mixed solution, and the iron-containing compound is iron oxide; S5, at room temperature, adding the washed synthetic filter cake obtained in step S4 into deionized water, breaking it up and stirring it evenly, then adding sulfuric acid, then heating it to 70°C and crystallizing it under stirring until the material turns crystal and turns white, lowering the stirring speed and keeping the temperature for reaction for 2 h, filtering after the reaction to obtain an aged filter cake and an aged mother liquor, and washing the aged filter cake with deionized water, wherein the molar amount of sulfuric acid is 0.2 times the molar amount of iron in the synthetic filter cake; S6, placing the washed aged filter cake obtained in step S5 in an oven, drying it at 120° C. for 18 h to obtain ferric phosphate dihydrate, placing the ferric phosphate dihydrate in a muffle furnace and sintering it at 560° C. to obtain anhydrous ferric phosphate finished product.

Citation Information

Patent Citations

  • Method for preparing battery grade iron phosphate from waste and old lithium iron phosphate batteries

    CN109179358A

  • Method for recovering iron phosphate from lithium iron phosphate extraction slag and application thereof

    CN115196609A